Pengaruh pemberian aditif cair buah naga merah (Hylocereus polyrhizus) terhadap performa burung puyuh betina umur 16-50 hari (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2015)
The research aimed to know the effect of a liquid additive red dragon fruit (Hylocereus polyrhizus) on the performance of quail females aged 16-50 days with different treatment. The research was conducted at cage of Non Ruminant Feed Nutrition Science Laboratory, Department of Animal Nutrition and Feed, Animal Agriculture Faculty, Diponegoro University on September-December 2015. The research design based on Completely Randomized Design (CRD), with the control treatment and treatment liquid additives red dragon fruit twice a day, once a day and two days one. Each treatment was 5 times repeated. The parameters measured were feed consumption, weight gain, feed conversion and feed efficiency. The results showed that the treatment was not significant (P> 0.05) effects on feed consumption, weight gain, feed conversion and feed efficiency in quail. The average of T0, T1, T2 and T3 which feed consumption of 15.64; 15.85; 15.67 and 15.80 g/ head/day, weight gain of 118.70; 121.00; 124.20 and 126.90 g/head, feed conversion of 4.62; 4.58; 4.43 and 4.38 and feed efficiency of 21.68; 21.98; 22.65 and 22.92%. The conclusion is the treatment of a liquid additive red dragon fruit (Hylocereus polyrhizus) on quail resulted in feed consumption, weight gain, feed conversion and feed efficiency were similar to the control treatment that has not been able to improve the performance of quail aged 16-50 days. Keywords : quail, red dragon fruit, feed consumption, performances